2016
DOI: 10.1186/s12889-016-3585-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of intentional poisoning suicide during 1993-2013 in Ilam Province, Iran

Abstract: BackgroundSuicide is an important social tragic phenomenon which occurs by different tools or methods in different communities. Considering deliberate poisoning as a common and important method in Ilam province for suicide, the present study was launched to epidemiologically assess committing suicide in Ilam province, Iran, based on intentional poisoning.MethodsBy a retrospective study, all the recorded data associated with intentional poisoning suicide in Ilam Province during 1993–2013 were analyzed. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
(32 reference statements)
5
25
0
2
Order By: Relevance
“…In the study conducted in Ilam province in Western Iran, the highest incidence rate and suicide attempts were observed between 15 and 24 years. [9] A study in the city of Taubaté-SP identified that there was a predominance of incomplete grade 2, this for the individual exposed to suicide attempt. Some medical records did not have the information in question, being represented by the item "not applicable" (15.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study conducted in Ilam province in Western Iran, the highest incidence rate and suicide attempts were observed between 15 and 24 years. [9] A study in the city of Taubaté-SP identified that there was a predominance of incomplete grade 2, this for the individual exposed to suicide attempt. Some medical records did not have the information in question, being represented by the item "not applicable" (15.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Educational level, therefore, can be considered as a deterrent against suicide. [9] A study of suicide attempts by exogenous intoxication in Ceará, Brazil [10] found that it was higher among women (55%), followed by 45% among men. In the present study, however, the highest number of suicide attempts was among men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of data collection, numerous efforts were made for purposes of consistency to recruit women who had attempted various suicide methods, but four cases who used the self‐immolation method died after 1 month due to the severity of the injury, one case of attempted hanging was transferred to prison for criminal activity, and one case of rice‐tablet (aluminum phosphide) poisoning lost her ability to speak. Ultimately, all interviews were conducted with seven cases of suicide attempts by drug ingestion, which is the most common method of suicide attempt in Iran . Women who were willing to participate in the study entered into the research if the following criteria were met: being hospitalized due to a suicide attempt as a nonfatal, self‐directed, potentially injurious behavior with intent to die; aged 18 to 45 years old; able to speak in Farsi or Kurdish; and having no history of cognitive disorders such as schizophrenia that could disrupt the interview process .…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no published evidence available to explain the reasons why self‐immolation is chosen more frequently than other methods for suicide. Although self‐immolation is the most common method for achieving suicide in Iran, drug ingestion was the most common method used for those surviving a suicide attempt …”
Section: Introductionmentioning
confidence: 99%